Spatial Model for Food Security in Eastern Indonesia 2024 - Shohwah, Fathiyah Nur; Arufi, Imam Fathoni; Wicaksono, Mohammad Iqbal; Meilawati, Nadia Lutfi; Meilani, Nilam Cahya; Sohibien, Gama Putra Danu (Proceedings of The International Conference on Data Science and Official Statistics, 2025)
Food security is the condition of meeting food needs for the country down to the individual level, as measured by the availability, affordability, utilization, and stability of food. Despite being a basic human need, food security in Indonesia is not evenly distributed, especially in Eastern Indonesia. Based on these findings, this study aims to determine the general picture of food security and the factors influencing it in districts/cities in Eastern Indonesia in 2024. The method used is the Spatial Durbin Model (SDM) with an inverse distance weighting matrix. The results show that the variables Distribution of GRDP of Sector Agriculture, Forestry and Fishing, Poverty Rate, Average Years of Schooling, Lag of Food Security Index, Lag of Open Unemployment Rate, and Lag of Poverty Rate have a significant influence on the Food Security Index variable in districts/cities in Eastern Indonesia in 2024.